2006
DOI: 10.1097/01.pec.0000210178.86504.80
|View full text |Cite
|
Sign up to set email alerts
|

Parental Presence During Invasive Procedures and Resuscitation

Abstract: The physicians and nurses in the study population tended to prefer parents not to be present during procedures as the level of invasiveness increased. An agreement between the attitudes of physicians and nurses toward parental presence during invasive procedures is essential for improving quality of service, especially in the dynamic environment of the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
1
12
0
11
Order By: Relevance
“…Similar to other studies, the rate of parental willingness to attend is inversely related to the invasiveness of the procedure [23,34]. In published reports and practice, health professionals tend to discourage parental presence as the invasiveness of the procedure increases [37,45]. Among all the IPs, we noticed that a significant percent of parents declined attending lumbar puncture, in particular.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to other studies, the rate of parental willingness to attend is inversely related to the invasiveness of the procedure [23,34]. In published reports and practice, health professionals tend to discourage parental presence as the invasiveness of the procedure increases [37,45]. Among all the IPs, we noticed that a significant percent of parents declined attending lumbar puncture, in particular.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies of FCC and its components in Turkey showed that nurses viewed parents as those taking physical care of their children and mostly only meeting their physical care needs (Boztepe & Çavuşoğlu ; Kuzlu, Kalinci, & Topan, ). Parents did not generally stay with their children during painful procedures or CPR (Boztepe, ; Egemen, İkizoğlu, Karapınar, Coşar, & Karapınar, ). In the present study, it was also found that nurses understood the FCC philosophy and had concerns about parents being present when their child was receiving painful procedures or CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Egemen ve ark. [24] yaptıkları çalışmada sağlık personeli ebeveynlerin ağrılı işlemler sırası-na olmalarının işlemi engellemelerine veya işlemin başarısını olumsuz etkilemelerine ve çocuğu strese sokmaları gibi olumsuz etkilerinin olduğunu ifade etmişlerdir. Benzer şekilde Ellison [22] 227 hemşireyle yaptığı çalışmadan elde ettiği kalitatif bulgulara göre hemşireler; ailelerin ağrılı işlemlerde bulunmasının iş performanslarını olumsuz etkilediğini, ekstra zaman harcamaya neden olduklarını ifade etmişlerdir.…”
Section: Discussionunclassified